Pengembangan karakter peduli lingkungan pada peserta didik melalui outdoor learning di SD Peradaban Cilegon - Maulia Rahmawati; Reksa Adya Pribadi Reksa; Patra Aghtiar Rakhman (Universitas Sarjanawiyata Tamansiswa, 2026)
This study aims to describe the development of environmentally conscious character through outdoor learning at SD Peradaban Cilegon using a descriptive qualitative approach. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman model. The results of the study indicate that: (1) planning is designed through the school's vision and mission in accordance with the objectives in various types of activities whose technical implementation is mutually supportive in the form of teaching modules and activity proposals; (2) outdoor learning activities were carried out through preliminary, core, and closing stages, including observation, environmental projects, agricultural practices, field trips, and nature exploration; (3) students' environmental awareness has shown awareness and concern for the environment through various simple actions, with students caring for the environment, reducing plastic use, and managing waste according to type. However, students still need habituation and guidance from teachers so that their environmental awareness becomes more consistent and develops into a part of their daily habits.